Lung Volume Reduction for Emphysema and The Canadian Lung Volume Reduction (CLVR) Surgery Project - John D Miller; Richard A Malthaner; Charles H Goldsmith; Gerard Cox; David Higgins; David Stubbing; Allan Kitching; Toni E Newman; Ellen McDonald (Canadian Respiratory Journal, 1999)
OBJECTIVE: To review the literature on the surgical treatment of emphysema and to present preliminary results from a pilot study of lung volume reduction (LVR) surgery.